2008
DOI: 10.1111/j.1365-2842.2008.01869.x
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal components of class III malocclusions and compensation mechanisms

Abstract: The aim of this retrospective study was to assess the skeletal characteristics of sagittal maxillary and mandibular discrepancies resulting in class III malocclusions and compensation mechanisms in one Caucasian European population (Croatian). The study sample included 107 patients (63 females and 44 males), aged between 11 and 18 years of age (mean age 14.6 +/- 2.2), with a class III malocclusion. Forty-three angular and linear measurements were assessed from the pre-treatment lateral cephalographs of each su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
5
15
0
Order By: Relevance
“…Our results showed that the subjects with class III malocclusion had larger mandibles (B-y distance) and prominent soft tissue pogonion. In accordance with our results, several studies 1,13,16 showed that there was a tendency of more horizontal growth pattern in the mandibles of Class III subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that the subjects with class III malocclusion had larger mandibles (B-y distance) and prominent soft tissue pogonion. In accordance with our results, several studies 1,13,16 showed that there was a tendency of more horizontal growth pattern in the mandibles of Class III subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Singh et al 14 Our results showed that the subjects with class III malocclusion had larger mandibles (B-y distance) and prominent soft tissue pogonion. In accordance with our results, several studies 1,13,16 showed that there was a tendency of more horizontal growth pattern in the mandibles of Class III subjects.…”
Section: 13supporting
confidence: 81%
“…2 According to Spalj et al, 13 Class III subjects with maxillary retrognathia have an increased vertical growth pattern. In a cross sectional study, Bacetti et al 17 studied craniofacial characteristic of 1091 class III children and found a growth trends toward accentuated Class III profile and increased vertical facial dimension towards the late developmental stages.…”
mentioning
confidence: 99%
“…It is interesting to note that the dentoskeletal features of Joanna of Austria are similar to those of Class III European white subjects with maxillary retrognathism who demonstrate a tendency toward vertical growth as a possible compensation mechanism of Class III malocclusion. 26 On the contrary, Class III subjects with mandibular prognathism tend to exhibit a horizontal facial growth pattern and typically include more pronounced dentoalveolar compensation, that is, proclination of maxillary and retroclination of mandibular incisors. 26 The Class III long-face profile that affected Joanna of Austria is clearly testified by the portraits of the noble woman ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…26 On the contrary, Class III subjects with mandibular prognathism tend to exhibit a horizontal facial growth pattern and typically include more pronounced dentoalveolar compensation, that is, proclination of maxillary and retroclination of mandibular incisors. 26 The Class III long-face profile that affected Joanna of Austria is clearly testified by the portraits of the noble woman ( Figure 5). Joanna appears with a peculiar type of ''Habsburg jaw'' as the Class III profile was related to the presence of a marked maxillary retrusion rather than to mandibular prognathism.…”
Section: Discussionmentioning
confidence: 99%